SOUTH AMERICA: ASPECTS OF SECURITY: EDITORIAL (Glocalism: Journal of Culture, Politics and Innovation, 2025)
This section of Glocalism focuses on security challenges of or related to South America. It studies security using a widened security agenda, based on the sectoral theory of the Copenhagen School, including not only military security, but also political, economic, societal and environmental security sectors.